How do you multiply #(x-2)(x-3)#?

2 Answers
Jul 21, 2018

Answer:

#x^2-5x+6#

Explanation:

We can use the highly useful mnemonic FOIL (Firsts, Outsides, Insides, Lasts). This is the order we multiply in. We get

  • Multiply the first terms: #x*x=x^2#
  • Multiply the outside terms: #x*-3=-3x#
  • Multiply the inside terms: #-2*x=-2x#
  • Multiply the last terms: #-2*-3=6#

Putting it all together, we get

#x^2-3x-2x+6#, or #x^2-5x+6#

Hope this helps!

Answer:

#x^2-5x+6#

Explanation:

#(x-2)(x-3)#

#=(x-2)\cdot x-(x-2)\cdot 3#

#=x^2-2x-3x+6#

#=x^2-5x+6#